ALOKASI ANGGARAN BELANJA SEKTOR TRANSPORTASI DALAM ANGGARAN PENDAPATAN DAN BELANJA DAERAH KOTA DEPOK TAHUN ANGGARAN 2006-2010 - Christine Siahaan, Febi; Valiant Salomo, Roy (Jurnal Transportasi, 2012)
This study aimed to identify the position of the transport sector in strategic policy and allocation of Revenue and Expenditure of Depok and to evaluate the consistency of strategic policy with budget allocations in the transportation sector. The study was conducted with a qualitative approach. Data was collected by reviewing the various policy documents and interviewing relevant parties. The findings of this study is that transport strategicpolicy in Depok has been given a priority position. In accordance with the mission of medium and long term development, the transportation development puts a high priority on infrastructure development. The budget allocation for the transport sector consistently ranked in the top ten recipients of budget direct allocation.Keywords: budget allocation, strategic policy, transport infrastructure